2014
DOI: 10.5811/westjem.2014.5.20894
|View full text |Cite
|
Sign up to set email alerts
|

Who's Boarding in the Psychiatric Emergency Service?

Abstract: IntroductionWhen a psychiatric patient in the emergency department requires inpatient admission, but no bed is available, they may become a “boarder.” The psychiatric emergency service (PES) has been suggested as one means to reduce psychiatric boarding, but the frequency and characteristics of adult PES boarders have not been described.MethodsWe electronically extracted electronic medical records for adult patients presenting to the PES in an urban county safety-net hospital over 12 months. Correlative analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 13 publications
0
8
0
1
Order By: Relevance
“…That being the case, these patients carry a significantly higher risk and are difficult to manage in any circumstances. The challenges are magnified in emergency settings due to the physical limitations and the lack of consistency in staffing [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That being the case, these patients carry a significantly higher risk and are difficult to manage in any circumstances. The challenges are magnified in emergency settings due to the physical limitations and the lack of consistency in staffing [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…In that study, prolonged LOS was associated with suicidal ideation, disposition to an inpatient unit, homicidal ideation, lack of insurance, homelessness, male gender, past history of psychiatric hospitalization, diagnosis of substance abuse, significant psychiatric co-morbidity (represented by three or more Axis I diagnoses), and diagnosis of a psychotic disorder. Another study was also conducted in the PES but used boarding as the primary outcome [ 34 ]. The study concluded that boarding was associated with referral by a party other than the patient, arrival on or just after the weekend, arrival in restraints, physical restraint or seclusion in the PES, referral for involuntary hospitalization, primary anxiety disorders or personality disorders, and tobacco use.…”
Section: Introductionmentioning
confidence: 99%
“…To that end, we found that 73% of transferred patients with a primary psychiatric diagnosis met the criteria for boarding. Other studies found that rates of boarding ranged from 9.7% to 27.5% (24, 36, 37); however, one survey found that greater than 30% of EDs board at least 75% of all patients (38). Our rate of boarding was likely high due to our sample characteristics (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Die Analyse der "Zugangskarrieren" von Notfallpatienten könnte hierbei den Anteil der Wirkungen durch die Fragmentierung und die Lücken des Versorgungssystems z. B. am Wochenende im Unterschied zu patientenbezogenen Faktoren sichtbar machen, wie es US-Autoren nachweisen konnten [4].…”
Section: Introductionunclassified